Islamic Social Finance and Sustainable Development Goals: Issues and Challenges - Rosman, Romzie; Redzuan, Nur Harena; Mokhtar, Nor Zainiyah Norita; Engku Ali, Engku Rabiah Adawiah; Mohammed, Mustafa Omar (Journal of Islamic Finance, 2022)
Islamic finance is an important driver to support the implementation of sustainable development goals. Theoretically, the core principle of Islamic finance aligns with the sustainable development goals. Moreover, the application of Islamic social finance instruments especially zakat, waqf, and sadaqah can be managed efficiently and effectively to support the specific sustainable development goals. However, there are many issues and challenges in the understanding and application of Islamic social finance, and some perceptions of the sustainable development goals agenda from the Islamic perspective. This study firstly discussed the concept of Islamic social finance and discusses each Islamic social finance instrument. Then, a qualitative research method based on Focus Group Discussion was employed to investigate the issues and challenges of Islamic social finance to support the sustainable development goals. The findings include an investigation and discussion on the important themes which are on: (1) the definition of Islamic social finance; (2) the relation of Maqasid Shariah and sustainable development goals in Islamic social finance; (3) The application of Islamic social finance in eliminating poverty; and (4) the issues and concern in the utilization of Islamic social finance to improve socio-economic well-being. The study suggests a more focused definition of Islamic social finance as a subset of Islamic finance; and the findings may enhance the policy implication, especially on the application of Islamic social finance instruments due to their unique characteristics as compared to the widely use Islamic financial instruments.